Systematics of Afrotropical Eristalinae (Diptera: Syrphidae) using mitochondrial phylogenomics. (11th January 2022) - Mullens, Nele; Sonet, Gontran; Virgilio, Massimiliano; Goergen, Georg; Janssens, Steven B.; De Meyer, Marc; Jordaens, Kurt
Abstract: We examined the phylogeny and intrageneric classification of eristaline hoverfly genera from the Afrotropical Region using mitochondrial genomes. Genome skimming was used to obtain (nearly) full mtDNA and nuclear rDNA (18S, 28S) genomes of 120 museum vouchers from eight genera and 98 species. Phylogenetic reconstructions of mitogenomes and mitogenomes + nuclear rDNA yielded comparable phylogenies while that of rDNA only resulted in poorly resolved phylogenies. Phylogenetic analyses focused on six genera and supported the monophyly of the genera Chasmomma Bezzi, Eristalinus Rondani, Mesembrius Rondani and Syritta Le Peletier & Serville, whereas Simoides Loew was not monophyletic and rendered Phytomia Guérin‐Méneville paraphyletic. We therefore synonymize Simoides with Phytomia . Within Chasmomma, two species‐groups that differ in the colour and the shape of the hind femora ( Chasmomma femoratum and Chasmomma nigrum species‐groups) were supported. Within Eristalinus, the monophyly of the subgenera Merodonoides Curran and Eristalodes Mik was supported, but not of the subgenus Eristalinus Rondani. Within Syritta, the monophyly of three out of the five species‐groups tested was rejected. This approach illustrates the importance of integrative and iterative approaches in taxonomy and shows that genomic data may not only clarify the systematic relationships among hoverfly genera and species, but also offer perspectives into the evolution of morphological and ecological variation within the family. Abstract : The first large‐scale phylogenetic study using full mitochondrial DNA to resolve species relationships in Afrotropical Diptera. Mitogenomics resolves species phylogenetic relationships in Afrotropical hoverflies (Syrphidae) and provides hypothesis for future taxonomic studies. The genus Simoides Loew, 1858 is synonymized with Phytomia Guérin‐Méneville, 1834.